New records for two Peruvian endemic Telipogon (Orchidaceae) including an unexpected record of Telipogon ariasii - Martel, Carlos (2016)
The paper registers for first time to Telipogon selbyanus in southern Peru and new records to Telipogon ariasii. A new record of Telipogon ariasii was found surprisingly ca. 2000 m a.s.l. below the type location. Herein I provide taxonomic notes, a distribution map and the updated conservation status of both species.